Living with predators at the larval stage has differential long-lasting effects on adult life history and physiological traits in two anopheline mosquito species. (May 2021) - Roux, Olivier; Renault, David; Mouline, Karine; Diabaté, Abdoulaye; Simard, Frederic
Graphical abstract: Highlights: Life history traits and all the nutritional reserves were negatively affected. An. coluzzii suffer less from stress than An. gambiae. Differential nutrient assimilation to fulfill fitness or to fuel fight-or-flight response. Adaptation to chronic stress to decrease the cost of long-term exposure. Abstract: 1. Under predation stress, individuals increase their metabolic rate and adopt different resource allocation strategies to favor their direct survival to the detriment of growth, reproduction and self-maintenance. Species and sexes are both faced with different physiological and life history demands and should adopt different strategies which lead to carry-over effects on adult metabolic reserves and on oxidative status. 2. Malaria mosquitoes Anopheles coluzzii and An. gambiae are sibling species. In nature, their larvae are exposed to different levels of predation risk and An. coluzzii larvae are more capable of surviving predation threats than An. gambiae, because of a better ability to gauge the threat level and to produce an adapted behavioral response. Impact of this response on adult physiology is however unknown. 3. Here, we investigated the carry-over effects of larval predation stress: first, on life history traits such as development length, size and weight at emergence, fecundity and survival; second, on metabolic resources at emergence such as lipids, proteins, carbohydrates and amino acids; and third, on oxidative status with the total anti-oxidant capacity and the oxidation of proteins in the two species and in both sexes. 4. We found that on one hand, it took more time for An. coluzzii to develop in presence of a predator and they emerged with a smaller size but a similar weight as control individuals. On the other hand, An. gambiae exposed to predators developed as fast as controls but with both a smaller size and a smaller weight. Fecundity was negatively impacted in both species following exposure to predation threats. Teneral reserves were affected depending on the species and the sex. The total anti-oxidant capacity of individuals exposed to stress was lower than in the controls but a significant level of damages to proteins was detected in An. gambiae males only. 5. Our findings suggest that predation stress induces very different physiological responses even in closely related species and between sexes. Allocation of resources in larvae may differ and depend on the species' aptitude to develop in presence of predators and on the sex, since males and females might adopt different strategies to fulfill their fitness.